Tolerability and Effectiveness of Switching to Dulaglutide in Patients With Type 2 Diabetes Inadequately Controlled With Insulin Therapy - Kim, Youngsook; Huh, Ji Hye; Lee, Minyoung; Kang, Eun Seok; Cha, Bong-Soo; Lee, Byung-Wan (Frontiers in Endocrinology, 2022)
Aims: Glucagon‐like peptide 1 (GLP-1) receptor agonists have demonstrated strong glycemic control. However, few studies have investigated the effects of switching from insulin to GLP-1 receptor agonists. We aimed to investigate, using real-world data, whether switching to dulaglutide improves glycemic control in patients with type 2 diabetes mellitus (T2D) inadequately controlled with conventional insulin treatment. Materials and methods: We retrospectively evaluated 138 patients with T2D who were switched from insulin to dulaglutide therapy. We excluded 20 patients who dropped out during the follow-up period. The participants were divided into two groups according to whether they resumed insulin treatment at 6 months after switching to a GLP-1 receptor agonist (group I) or not (group II). A multiple logistic regression analysis was performed to evaluate the parameters associated with the risk of resuming insulin after replacement with dulaglutide. Results: Of 118 patients initiated on the GLP-1 receptor agonist, 62 (53%) resumed insulin treatment (group I), and 53 (47%) continued with GLP-1 receptor agonists or switched to oral anti-hypoglycemic agents (group II). Older age, a higher insulin dose, and lower postprandial glucose levels while switching to the GLP-1 receptor agonist were associated with failure to switch to the GLP-1 receptor agonist from insulin. Conclusions: A considerable proportion of patients with T2D inadequately controlled with insulin treatment successfully switched to the GLP-1 receptor agonist. Younger age, a lower dose of insulin, and a higher baseline postprandial glucose level may be significant predictors of successful switching from insulin to GLP-1 receptor agonist therapy.